Stakeholders' Views on E-cigarette Legislation: A Qualitative Study in Taiwan - Shih, Chin-Shui; Etter, Jean-Francois (Frontiers in Public Health, 2019)
Objectives Little is known about stakeholders’ opinions on e-cigarette legislation in Taiwan. Our aim is to understand the perspectives of stakeholders regarding the current legal system and measures that could be included in future e-cigarette legislation in Taiwan. Material and Methods We conducted in-depth interviews with 14 Taiwanese stakeholders, using semi-structured questionnaires, either face-to-face or via telephone, in 2016-2017. All interviews were transcribed. Results The current legal system is applied to e-cigarettes even though it does not mention them specifically, this system carries risks and faces challenges from anti-tobacco and vaper groups. Some weaknesses in the current legislative framework were noted, including the facts that e-cigarettes are sold without government approval, that there are no manufacturing standards, no inspections or monitoring, and no regulations for usage or advertising. There was wide acceptance among stakeholders that e-cigarettes should be better regulated, particularly e-cigarettes containing nicotine. Most interviewees agreed that there is a need to restrict e-cigarette use by teenagers and in public places where tobacco smoking is prohibited. Most interviewees also would like to restrict marketing, ban sales in vending machines, via mail order, and over the internet; label content and nicotine levels; and introduce health warnings and taxation. Conclusions Almost all interviewees agreed that there is a need for a specific legal framework for e-cigarettes in Taiwan, and that e-cigarettes should be regulated in the same way as combustible cigarettes.